2003
DOI: 10.1080/15216540310001640498
|View full text |Cite
|
Sign up to set email alerts
|

Small Heat‐shock Proteins and Clusterin: Intra‐ and Extracellular Molecular Chaperones with a Common Mechanism of Action and Function?

Abstract: Small heat-shock proteins (sHsps) and clusterin are molecular chaperones that share many functional similarities despite their lack of significant sequence similarity. These functional similarities, and some differences, are discussed. sHsps are ubiquitous intracellular proteins whereas clusterin is generally found extracellularly. Both chaperones potently prevent the amorphous aggregation and precipitation of target proteins under stress conditions such as elevated temperature, reduction and oxidation. In doi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
185
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(194 citation statements)
references
References 43 publications
7
185
0
2
Order By: Relevance
“…CLU mRNA is widely expressed (de Silva et al 1990) and the mature CLU product is secreted out of the cell to serve as an extracellular chaperone (Carver et al 2003;Wyatt et al 2009). Secreted CLU is a heavily glycosylated, 75-80-kDa heterodimeric protein that is linked by five disulfide bonds (Choi-Miura et al 1992).…”
Section: Clusterinmentioning
confidence: 99%
“…CLU mRNA is widely expressed (de Silva et al 1990) and the mature CLU product is secreted out of the cell to serve as an extracellular chaperone (Carver et al 2003;Wyatt et al 2009). Secreted CLU is a heavily glycosylated, 75-80-kDa heterodimeric protein that is linked by five disulfide bonds (Choi-Miura et al 1992).…”
Section: Clusterinmentioning
confidence: 99%
“…Since that time many studies have shown that clusterin has chaperone activity similar to that of the small heat-shock proteins (sHsps) [22,23,[26][27][28][29]33]. At substoichiomentric concentrations, clusterin inhibits the stress-induced amorphous aggregation of a large number of unrelated client proteins by binding, in an ATP-independent manner, to areas of exposed hydrophobicity on partially unfolded intermediates [22,[26][27][28][29]31].…”
Section: In Vitro Chaperone Activitymentioning
confidence: 99%
“…As a result, it is unlikely that detailed X-ray crystal structures of full-length casein protein will be achieved; however, three-dimensional energy-minimized molecular models are available [203,204]. Two of the casein proteins, α S1 -and β-casein, have been found to have molecular chaperone-like activity, similar to the small heat shock proteins (sHsps) [26,92]. The open, flexible nature of α S1 -casein and β-casein results from the high percentage of proline residues in their amino acid sequence (9% of the amino acid sequence of α S1 -casein and 18% of β-casein) and lack of disulfide bonds.…”
Section: Caseinsmentioning
confidence: 99%
See 2 more Smart Citations